Evaluasi Kebijakan Cap Elektronik Keimigrasian, Data Biometrik, dan Mesin Autogate Dalam Konsep Geopolitik - Gede Maha Aditya Pramana; Intan Nurkumalawati; Ridwan Arifin (Jurnal Ilmiah Kebijakan Hukum, 2022)
Immigration Border Control (TPI) at Bali Ngurah Rai Airport adopts electronic entry sticker, biometric data collection, and autogate machines called the Immigration Movement Application System (APK). The system is equipped with a scanner that records facial biometric data and fingerprints of foreigners upon arrival. However, there are problems in implementing this system at the related TPI. This study evaluates immigration inspection policies, especially the process of taking biometric data, giving electronic entry stamps, and autogate machines at TPI Ngurah Rai Airport. This research uses qualitative research method with a public policy evaluation approach based on observations and document analysis. The results of this research show that the concept of biometric border control at TPI is not fully relevant to the concepts in the international provisions of ICAO Doc 9303 and ICAO TRIP Guide 2018. The Ministerial Regulation Number 28 of 2018  on Immigration Stamp and Circular Letter No. IMI.1-UM.01.01-5.7755 needs to be evaluated and revised to include four stages of checking with electronic stamps and system synchronization with autogate machines. This immigration clearance model at TPI applies a geopolitical concept that focuses on territorial/regional borders rather than a biopolitical concept that focuses on security risks for individuals.